CRUSTAL AND UPPERMOST MANTLE VELOCITY STRUCTURE OF NORTHERN EURASIA ALONG THE PROFILE QUARTZ - Schueller W.; Morozov I.B.; Smithson S.B. (My University, 1997)
The velocity structure of the crust and uppermost mantle beneath the DSS profile Quartz in northwestern Russia is determined using a linearized seismic tomography scheme. The analysis is performed on the northern 2200 km of the profile spanning from the Kola Peninsula, the Timan-Pechora basin, and the Uralian fold belt to the west Siberian basin. Refracted and reflected phases recorded from 28 chemical and two nuclear shot points are analyzed. The inversion technique allows determination of the P-wave velocity structure and estimation of the depth of the crust-mantle discontinuity. Resolution analysis shows that the upper crustal structure and sections of the lower crust and uppermost mantle are well resolved. The modeled velocity and crustal thickness anomalies are con-firmed by the resulting structure of the resolution matrix. Poorer ray coverage in parts of the lower crust and most sections of the uppermost mantle limits their resolvable structures. A thick (over 10 km), high-velocity block (Vp > 7.0 km/sec) in the lower crust of the Precambrian beneath the Kola Peninsula; crustal thinning and a wide range of compressional velocities in the sedimentary basin structures; and a significant crustal root beneath the Uralian fold belt (42 to 45 km Moho depth with high lower crustal velocities exceeding 7.0 km/sec) were identified in the tectonic structure of north-western Eurasia.
Keywords: Precambrian; Precambrian; Докембрий